The Microbiome and Probiotics in Childhood - Hsieh, Michael Harrison (Seminars in Reproductive Medicine, 2014)
Infants, from the moment of birth, are colonized by large numbers of microbes. This colonization continues throughout childhood and from preliminary studies seems to be a highly dynamic process, even during the usual physiologic state we refer to as health. In this context, the persistence of bacterial and fungal species in and on the human body likely confers various benefits to the host. One specific approach to modulate such beneficial effects is the administration of probiotics, also known as beneficial microbes. Herein, we outline the highest level evidence in regard to the evolution of the microbiome during childhood and its manipulation by probiotics for genitourinary, enteric, and allergic and atopic disorders. Thus, probiotic approaches are promising alternatives and adjuvants to traditional vaccines and antibiotics. This may usher in a new age in which vaccine and antibiotic side effects and antibiotic resistance are minimal issues in the setting of maintaining children's health and prevention of disease.
Keywords: probiotics; children; microbiome